Icitrap - an experiential training exercise for examining participatory approaches to project management - Dearden, Philip (1999)
Icitrap is a flexible workshop-based training exercise that has been developed to examine and evaluate participatory approaches in project management. This article outlines the background and rationale for the commissioning of the Icitrap exercise and then describes the development and testing methodology used. The experiential nature of the exercise is the key to the fulfilment of its stated aim, which is to foster an understanding of participatory approaches towards project management by drawing out common problems, principles and points for action. Details of the finalized experiential training package, available in text-based and electronic formats, are presented. - Reproduced
Keywords: Project management